Fatigue in chronic liver disease patients: prevalence, pathophysiology, and management - Artur Kośnik; Maciej Wójcicki (Gastroenterology Review)
Fatigue is the most commonly encountered symptom in patients with chronic liver disease (CLD). The resulting decrease in quality of life contributes markedly to the societal costs of fatigue. Moreover, fatigue is associated with social dysfunction, increased daytime somnolence, impaired working ability, and increased risk of mortality. Fatigue is not related to the severity of the underlying liver fibrosis or dysfunction. In CLD patients, fatigue manifests with both central symptoms, characterised by cognitive impairment, sleep disturbance, apathy, and autonomic dysfunction, and peripheral symptoms, characterised by decreased exercise tolerance and reduced physical activity levels. The pathogenesis of fatigue in CLD is multifactorial and involves changes in the brain–liver axis resulting from changes in inflammatory cytokines or the gut microbiome. Numerous interventions have attempted to alleviate fatigue in CLD by improving its central and peripheral manifestations or the underlying liver disease. Currently, however, there are no widely accepted or effective treatments for fatigue in CLD patients. In this review, we highlight the problem of fatigue in CLD, the current theories regarding its pathogenesis, and current approaches to its treatment.